Systemic and Local Immunological Markers in Preeclampsia - Almagul Kurmanova; Altynay Nurmakova; Damilya Salimbayeva; Gulfiruz Urazbayeva; Gaukhar Kurmanova; Natalya Kravtsova; Zhanar Kypshakbayeva; Madina Khalmirzaeva (Diagnostics, 2025)
Preeclampsia (PE) is one of the main causes of obstetric complications and leads to both maternal and neonatal mortality. The maternal innate immune system plays an important role throughout pregnancy by providing protection against pathogens, while simultaneously inducing tolerance to a semi-allogenic developing fetus and placental development. Background/Objectives: To conduct a comparative study of immunological markers in the blood and placenta in preeclampsia. Methods: A total of 35 pregnant women were enrolled in a comparative study with preeclampsia (7) and with physiological pregnancy (28). A study of the immune status in peripheral blood and placenta was conducted with an examination of the subpopulation of lymphocytes profile and intracellular cytokines production by flow cytometry. Results: In the blood of pregnant women with PE, there was a decrease in CD14+ monocytes, as well as a significant increase of natural killers CD16+, CD56+ and activation markers HLA-DR+ and CD95+, as well as a significant rise in production of IL-10, TNF, Perforin, GM-CSF, and IGF. At the same time, in placental tissue in patients with preeclampsia, on the contrary, a significant decrease in regulatory cells CD4+, CD8+, CD14+, CD56+, CD59+, activation markers CD95+, as well as anti-inflammatory cytokine IL-10, growth factors VEGFR and IGF was detected. Conclusions: The maternal–fetal immune profile is crucial for successful fetal development and dysregulation of T-, B-, and NK cells can contribute to inflammation, oxidative stress, and the development of preeclampsia.